2009
DOI: 10.1136/adc.2008.153577
|View full text |Cite
|
Sign up to set email alerts
|

Loss of triglycerides and carotenoids in human milk after processing

Abstract: Mature human milk can be stored safely in a freezer and heated in a microwave oven without loss of fat or carotenoids. The clinically important loss of fat during tube feeding is probably the most important contributing factor to the decrease in lutein and beta-carotene in tube feeding, with only a small role for peroxidation during light-exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…There have been very few works published in this regard. Tacken et al 10 studied 30 samples frozen at -18°C for 28 days and did not find any significant differences in the concentration of fat using a colorimetric method. Friend et al 15 studied in 20 samples (10 frozen slowly and 10 quickly) with the Roese-Gottlieb method the concentration of fat after 1 week, 1 month, and 3 months from freezing at -20°C; this study found a decrease, although this was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There have been very few works published in this regard. Tacken et al 10 studied 30 samples frozen at -18°C for 28 days and did not find any significant differences in the concentration of fat using a colorimetric method. Friend et al 15 studied in 20 samples (10 frozen slowly and 10 quickly) with the Roese-Gottlieb method the concentration of fat after 1 week, 1 month, and 3 months from freezing at -20°C; this study found a decrease, although this was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…2,10,17,18,[24][25][26] Consequently, peroxidation of both free fatty acids and those bound to glycerol (tri-and diglycerides) occurred, leading to a physicochemical modification in these. The fatty acids with their structure modified would not be quantified by HMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important ones are β-carotene and lycopene. Lutein concentrations in human milk range from approximately 3-237 mg/L (Bettler et al, 2010;Canfield et al, 2003;Jewell et al, 2004;Tacken et al, 2009). Taken together lutein and zeaxanthin account for 28% of total (Song et al, 2012 In colostrum the carotenoid pattern resembled those of plasma and the low-density lipoprotein fraction.…”
Section: The Role Of Lutein On Infant Nutritionmentioning
confidence: 99%
“…Studies about the effects of time spent at -20°C on macronutrients (fat, protein, and lactose) and energy content are scarce. 9,10,11,12 Scientific evidence about nutritional quality losses during this procedure is needed. 12,13 The availability of fat in human milk is influenced by the duration of pregnancy, the number of postpartum months, the volume of milk produced, the time of breastfeeding, the mother's diet, and the mother's weight gain during pregnancy.…”
mentioning
confidence: 99%